Pengaruh Komposisi Media Tanam dan Konsentrasi Pupuk Organik Cair Daun Kelor (moringa oleifera L.) terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) - Putri, Retno Ariny Savari; Usmadi, Usmadi (Berkala Ilmiah Pertanian, 2024)
This study aims to determine the effect of the composition of the planting medium with the concentration of liquid organic fertilizer of Moringa leaves on the growth and yield of shallot plants. This research was conducted in October 2022 - March 2023 in the greenhouse of the Soil Science Study Program, Faculty of Agriculture, University of Jember. The study used a completely randomized design with 2 factors, there were 16 treatment combinations, 3 repetitions, and each repetition there were 3 experimental units, so that 144 experimental units were obtained. The first factor is the composition of the planting medium consisting of control; soil: cow manure (1:2); soil: cow manure (2:2) and soil: cow manure (3:2). The second factor was the concentration of liquid organic fertilizer for moringa leaves which consisted of control; 20ml/l; 50 ml/l and 80ml/l. The results showed that there was an interaction effect between the treatment of the composition of the planting medium and the concentration of liquid organic fertilizer of Moringa leaves on the fresh weight of the tubers and the dry weight of the tubers. The treatment of the composition of the planting media was able to increase the growth and yield of shallot plants, and the addition of liquid organic fertilizer for Moringa leaves was able to increase the growth and yield of shallot plants.